Primary bilateral plasmablastic lymphoma of the testis in a human immunodeficiency virus positive man - Badyal, Rama Kumari (Indian J Sex Transm Dis AIDS, 2015)
Human immunodeficiency virus (HIV)-related lymphomas are predominantly aggressive B-cells lymphomas. The most prevalent of the HIV-related lymphomas are diffuse large B-cell non-Hodgkin's lymphoma (NHL), which includes primary central nervous system lymphoma, and Burkitt lymphoma, whereas primary effusion lymphoma, plasmablastic lymphoma (PBL), and classic Hodgkin lymphoma are far less frequent. Of these, PBL is relatively uncommon and displays a distinct predilection for presentation in the oral cavity. In this manuscript, we report a primary testicular form of PBL in 44 year-old Border Security HIV positive patient who presented with bilateral testicular swelling of 1-year duration. On cytopathological and subsequent histopathological examination, the diagnosis of bilateral plasmablastic NHL was made. Extensive systemic work-up failed to reveal any disease outside the testes. Immune suppression rather than HIV itself is implicated in the pathogenesis of lymphomas. Herein, we report a case of PBL as AIDS-related malignancy presenting in testes and its correlation with CD4+ count.